Tax Policy and Trade Liberalization : An Application to Mexico - Feltenstein, Andrew (Washington, D.C. : International Monetary Fund, 1992)
We construct a dynamic general equilibrium model of an open economy and use it to examine issues of trade liberalization in Mexico. In particular, we consider the fiscal implications of quotas and tariffs and, accordingly, their removal. We show that, in the short run, there may be negative revenue effects from tariff liberalization, so that it may be necessary to raise domestic taxes to compensate for the tariff reduction. We also show that these results are highly sensitive to behavioral shifts in exports. Since such shifts are quite likely given the nature of the trade reform currently being undertaken, it is important that we qualify our results accordingly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet